The Pattern of Leadership of Women School Principals at the Al-Ulum Integrated Islamic Elementary School in Medan - Danny Abrianto; Hasrian Rudi Setiawan; Chandra Wijaya (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this research is to find out the pattern of leadership of female school principals in the Al-Ulum Integrated Islamic Elementary School in Medan. This type of research is descriptive qualitative, with the location of the study in the Al-Ulum Integrated Islamic Elementary School in Medan. Data collection methods used include: observation methods, interview methods and documentation methods. The results of this study are the principals' leadership in the Al-Ulum Integrated Islamic Elementary School in Medan showing leadership attitudes that are carried out with gentleness, example, humility and discipline in carrying out their duties. This is an increase in motivation for teacher performance, which is in his responsibility. Then, the pattern of leadership of female principals in the Al-Ulum Integrated Islamic Elementary School in Medan, namely providing guidance, direction and assistance for their employees.